2021
DOI: 10.1039/d0ma00980f
|View full text |Cite
|
Sign up to set email alerts
|

High modulus polyimide particle-reinforcement of epoxy composites

Abstract: A novel class of fully organic composite materials with well-balanced mechanical properties and improved thermal stability was developed by incorporating highly crystalline, hydrothermally synthesized polyimide microparticles into an epoxy matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…1 Additives, especially nanofillers, as well as the fabrication methods of composites, play a crucial role in polymer nanocomposite technologies, enabling the creation of materials with improved properties. [2][3][4][5][6][7][8][9][10] The nanotechnological approach not only includes adding nanofillers to the polymer matrix but also, more importantly, involves examining how the polymer matrix interacts with the extremely developed surfaces of nanofillers. Nanofillers of different types, both natural and functionalized, can be used to make polymer composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Additives, especially nanofillers, as well as the fabrication methods of composites, play a crucial role in polymer nanocomposite technologies, enabling the creation of materials with improved properties. [2][3][4][5][6][7][8][9][10] The nanotechnological approach not only includes adding nanofillers to the polymer matrix but also, more importantly, involves examining how the polymer matrix interacts with the extremely developed surfaces of nanofillers. Nanofillers of different types, both natural and functionalized, can be used to make polymer composites.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s, nanotechnology was originally presented as a brand‐new technique for enhancing the characteristics of polymer composites 1 . Additives, especially nanofillers, as well as the fabrication methods of composites, play a crucial role in polymer nanocomposite technologies, enabling the creation of materials with improved properties 2–10 . The nanotechnological approach not only includes adding nanofillers to the polymer matrix but also, more importantly, involves examining how the polymer matrix interacts with the extremely developed surfaces of nanofillers.…”
Section: Introductionmentioning
confidence: 99%
“…One literature study was found to report that hydrothermally synthesized PI powders were applied as an additive to increase the mechanical properties of other polymer resins. 44 There have been two studies that showed the possibility of sintering of hydrothermally synthesized PI powders (without the evaluation of mechanical properties). 45,46 In the present study, we first report the hydrothermal synthesis of semicrystalline PI powders along with the mechanical property evaluation of their compression-molded specimens.…”
Section: ■ Introductionmentioning
confidence: 99%
“…3,4,7,10,[15][16][17][18][19][20][21] The cured resin properties have been shown to get modified by the addition of fillers, diluents, plasticizers or accelerators according to the properties desired for the end-product. 17,[22][23][24][25][26][27] Amongst the additives, the addition of plasticizers to epoxy based resins reduces brittleness and prevents the brittle fracture by increasing the flexibility of molecular chains through hindered cross-linking. 4,22,28 Various types of organic plasticizers have been used in the past for epoxy systems.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,7,10,15–21 The cured resin properties have been shown to get modified by the addition of fillers, diluents, plasticizers or accelerators according to the properties desired for the end-product. 17,22–27…”
Section: Introductionmentioning
confidence: 99%